Leveraging graph-based semantic annotation for the identification of cause-effect relations - Susetyo Bagas Bhaskoro; Inkreswari Retno Hardini (International Journal of Electrical and Computer Engineering (IJECE), 2020)
This research is related to language article in Indonesia that discuss about causality relationship research used as public health surveillance information monitoring system. Utilization of this research is suitability of feature selection, phrase annotation, paragraph annotation, medical element annotation and graph-based semantic annotation. Evaluation of system performance is done by intrinsic approach using the Naive Bayes Multinomial method. The results obtained sequentially for recall, precision and f-measure are 0.924, 0.905, and 0.910.